(untitled) (Sociologisk Forskning, 2023)
Construction, reconstruction, deconstruction. Integration of theoretical perspectives. Intradisciplinarity and interdisciplinarity. Extradisciplinarity too. Openness to literature. Openness to new influences. Time spent mind-wandering. Inquiry into the past, present, and future. Responsiveness to a changing present. Readiness to reinvigorate old perspectives. Disclosure of other possibilities. Discovery of novel ideas. Clarification, elaboration, justification. Preflexivity and reflexivity. Intersubjectivity and communicativeness. No fixed eternal standard. If you have paid attention to the title for my essay, you might have noticed that it is a paraphrase of a pioneering article by Richard Swedberg (2016): “Before theory comes theorizing or how to make social science more interesting.” Like Swedberg I am highly interested in theorizing and creativity. In this short text, I will introduce a conceptualisation of that kind of thinking which per definition precedes the coming up with a novel idea. By the use of basic etymology, I have named this cognitive phenomena preflexivity (Engstam 2023). As thereby indicated, I propose that preflexivity, on an analytical level, comes before reflexivity. What I aim to highlight through the lens of preflexivity is the generative power of imaginative, loose, undecided thinking, as unbounded thought of this kind might, but only might, result in something novel coming up and thus give rise to prescientific impulses to clarify and elaborate that something into a rather sharp idea – perhaps an idea that will be recognized as really something. Without downplaying reflexivity, I accordingly emphasize the importance of preflexive thinking. To which extent following prescientific impulses is feasible depends on material conditions, however. Therefore, the possibilities for spending time thinking, discussing, and writing in a preflexive rather than reflexive manner are well worth considering for sociologists and other social scientists. And what about our style of thought? (Or perhaps: stylesof thought.) As sociologists we are overall more well-trained in convergent thinking than divergent thinking, even though results of divergent thinking might be of more interest to us. More specifically, our collective knowledge on how to take a methodical attitude towards an established phenomenon (Merton 1987), prepared to cure specified ignorance (ibid.), is larger than our knowledge on how to come up with novel ideas and make something unexpected out of them – a heretofore not established social phenomenon – through exploratory studies and creative theorizing (Swedberg 2014, 2016, 2020). Did you know that theories which are generally considered interesting deny certain collectively accepted assumptions? I did not until I read an interesting piece of work on “[the] sociology of phenomenology and [the] phenomenology of sociology” (Davis 1971). As far as the suggested theory on interestedness is correct, we may presume that research generally considered interesting by sociologist’s challenges one or more of those assumptions which we normally retain – almost as a rule. In other words, impactful theories stimulate us to think differently, because they break new ground for us! As per definition, it takes unnormal creativity to develop theories of that calibre; courage too, I would say, and on top of that self-confidence – temporarily unconstrained confidence in your intuition and the power of preflexivity. Impact and adequacy are different matters, though, and sometimes worlds apart. Strictly speaking, a break with the past is not always a breakthrough. What is truly valuable is not novel-only; in the light of our knowledge interests, it is advantageous too. This indicates the importance of finding adequate ways to investigate the adequacy of novel ideas. Doesn’t that too take unnormal creativity? One of the core ideas that constitute the growing field of theorizing is the conception of theories as fallible results of ongoing, veritably incompletable, relational, and historical production processes, driven by human problems, astonishment, consternation, and sometimes nothing less than despair. The world is rather messy, and not a very well-lighted place. And all of us who theorize – all theorizers of the world – are situated, embodied, and incomplete. As human beings of flesh and blood, we think and write for, with and against others; striving towards better answers to questions that are important to us; against the backdrop of enduring human conditions, attended patterns of continuity and change, and remarkable exceptions to what we had expected; drawing on a subset of what has already been said and written by members of the same thought collective; drawing on imagination and experience, as well; making use of creative and analytical thinking skills, from time to time under circumstances far from optimal; to produce another piece, mostly convergent or mostly divergent, and hopefully adequate-enough. ‘Theorizers’ is meant to indicate that not only so-called theorists theorize; likewise, we theorize when we do qualitative or quantitative research. Arguably, this holds not only for theorizing, but for philosophizing and criticizing as well. This sociological idea of theorizing (and theorizers) can be further pictured by reusing a thriving definition of sociology of philosophy, taken from Carl-Göran Heidegren´s and Henrik Lundberg´s introduction to this field (2018:10). In the following paraphrase, “sociology of philosophy” is replaced with “a sociological perspective on theorizing,” and so on: The vantage-point [from which to consider theorizing] is not a bloodless knowledge-making subject, but rather human beings, richly equipped with “the abilities of a creature who wants, feels, and think” (Dilthey 1833, xvii). Against this background, [a sociological perspective on theorizing] may be formulated as follows: From a [sociological] perspective, [scholarly thinking-and-writing] is conceived as a socially organized activity, anchored in different historical, social contexts; an activity that comprises the production of [theories], that is, propositions and arguments communicated with claims for validity. Behind every piece of theory, a person as well as a context is to be constructed, reconstructed, and deconstructed. As for me, I do not do sociology of philosophy, and not sociology of theorizing either. I rather theorize quite freely, drawing on a series of disciplines and traditions as described above – literature and lived experience too. Hence, I am more of a generalist than a specialist. Embodied, situated, and fallible, of course. Limited but curious. I try to extend my thinking through reading, listening, and looking at a lot. And I try to make something fruitful out of novel ideas that now and then come to my mind, usually those moments when I let my mind wander in silence. Occasionally I say to myself: You can think like a genius, even if you aren’t one – everybody can. Just let go! I am certainly not a philosopher, still a philosophizer. Perhaps I am not a theorist either, but for sure I theorize. And I try to theorize in an open, critical-theoretical manner. To do Sozialforschung. Even though I cannot. At least I do “something” – pensées and more. What about you? How do you come up with new ideas, yourself? Do you have good opportunities to clarify, elaborate, and justify them? Are you welcoming gifts of prescientific experience to your research? Do you follow your prescientific impulses? Or do you methodically push prescientific impulses away? Mind-wandering is great, even though the results of unconstrained thinking might not be great at all. Geniality is a matter of what you think, not a matter of how you think (cf. Engstam 2023). What comes to you when you think this way might be worthless; but on the other hand, it might not … That is something to explore subsequently through creative AND critical thinking, as well as openminded exploratory research, by yourself or together with people who are interested in the same not yet well-established social phenomenon. Clarification, elaboration, and justification involve something being clarified, elaborated, justified, and so on. This “something” is a result of thinking beforehand, in my words preflexively. What would be left if we could possibly reduce the life of the mind to a reflexive process of methodical critical thinking? A short preliminary answer is normal thinking. Doing vital and relevant sociology demands much more than that. I envision good sociology as an emerging web, responsively woven by touched free-spirited members of diverse thought collectives, interested in social phenomena and morally dedicated to progressive social change; each one of them begins anew by drawing new wefts across the warp of moral fiber, while simultaneously continuing and contributing to something much larger; thereby, different patterns appear as new sociologists join the ongoing effort, and others drop out or leave earth. I draw inspiration for this metaphor from the work of Hannah Arendt (1959), whose writings on “the human condition” are both eloquent and insightful. Particularly, her philosophizing on plurality, nativity, and mortality holds relevance when reflecting on the processes of theorizing, philosophizing, and criticizing. In the following paraphrase (cf. ibid.:10–11), I have replaced “human action” with “vital sociology,” and so forth: Plurality is the condition of [vital sociology] because we are all the same, that is, [sociologists AND] humans, in such a way that nobody is ever the same as anyone else who ever lived, lives, or will live. [Like all other] activities and their corresponding conditions, [sociology is therefore] intimately connected with the most general condition of human existence: birth and death, nativity and mortality. [—] The new beginning inherent in birth can make itself felt in the world only because the newcomer possesses the capacity of beginning something anew, that is, [of taking an initiative towards something a bit different]. Now, this is hopefully the right moment to round off with some curiosa! Descartes, the innovator of the method of doubt, in his youth considered three dreams that he dreamt on the night of 10–11 November 1619 as divine inspiration for his philosophy. “[T]he sentiment experienced by Descartes that he was invested by God with the mission of constituting the body of the sciences and thus, as a consequence, to establish true wisdom” has been reconstructed through readings of the young Descartes’ own account of his dreams and their interpretation in Olympica. Of the manifold questions that might be raised but never highlighted, one crucial question is the following: Was his very, very first idea of methodological skepticism discovered when dreaming?! In that case, we better not stick to the result!! Anyhow, to me the great philosopher seems to have been a highly preflexive thinker. Let’s make sociology more open! Let’s recognize the importance of prescientific experience! Let’s follow prescientific impulse to think further and explore! Let’s establish and reestablish social phenomena through truly exploratory research and creative theorizing! Let’s do free-spirited sociology! Only sometimes, it’s a good thing to know what you are doing. Anna Engstam Doctoral student at the Department of Sociology, Lund University Sandgatan 11, Box 114, 221 00 Lund anna_helena.engstam@soc.lu.se Acknowledgements For invaluable encouragement and responses on earlier drafts, I am grateful to Carl-Göran Heidegren, Richard Swedberg, Mikael Carleheden, and Sven-Olov Wallenstein.